The Distribution of Economic Rent within Global Value Chains in Resource Management - Evsukov, Sergey; Ustyuzhanina, Elena; Ustyuzhanin, Vladimir; Novikova, Ekaterina (International Journal of Supply Chain Management, 2019)
This research paper covers the distribution of economic rent among different participants of a chains, as exemplified by global value chains in the resource management industries. Five hypotheses on the value-added distribution in a chain were verified: (1) The larger the company, the more market power and advantages in value-added distribution it has; (2) The integrator of a chain (focal company) has more advantages in value-added distribution than other participants of a chain; (3) Suppliers of intellectual solutions have more advantages in value-added distribution than producers of goods; (4) The closer the company to the end consumer, the more advantages in value-added distribution it has; (5) Companies controlling market of final goods (brand or entry to the local market) have more advantages in value-added distribution than their suppliers. None of the mentioned above hypotheses are verified in accordance with empirical data in the selected sectors of economies. At the same time, it has been verified that investments in Research and Development, per se, do not guarantee any privileges in the international division of labor; suppliers of key parts are those who have clear advantages in value chains; localization of production of end goods is not always the right thing to do.